The Care Pathway Delays of Cervical Cancer Patient in Morocco - Hind Mimouni; Khalid Hassouni; Boujemaa El Marnissi; Bouchra Haddou Rahou; Leila Alaoui; Rachid Ismaili; Abderraouf Hilali; Leila Loukili; Rachid Bekkali; Ahmed Nejmeddine (Obstetrics and Gynecology International)
Introduction. The aim of this study is to document time intervals in cervical cancer care pathways, from symptom onset to disease detection and start of treatment, and evaluate how clinical, sociodemographic, and treatment factors influence delays throughout a patient’s clinical pathway. Methods. A retrospective study was conducted at the FEZ Oncology Hospital of the Hassan II University Hospital Center in Morocco. Results. 190 medical records of cervical cancer patients were collected. The dominant age group was 35–44, the median patient delay (PD) was 6 days, the median healthcare provider’s delay (HCP) was 21 days, the median referral delay (RD) was 17 days, the median diagnostic delay (DD) was 9.5 days, the median total diagnostic delay (TDD) was 16 days, the median treatment delay (TD) was 67 days, and the median health system interval (HSI) was 92 days. Multivariate analysis revealed that age was associated with the patient delay, the healthcare provider’s delay, the diagnosis delay, and the health system interval. The diagnosis year (the year in which the patient was diagnosed (either before 2012 or during 2012 as well as the other study years (from 2013 to 2017))), all investigations done prior to admission to the oncology hospital, and the age of first sexual activity were significantly associated with healthcare provider’s delay. Conclusion. The integration of a model and standard care pathway into the Moroccan health system is essential in order to unify cervical cancer care in the country.